Pelatihan Pembuatan Virtual Reality 3 Dimensi Safety Induction di PT. PLN Nusantara - Moh. Syaiful Anwar; Mochamad Shaleh; Feby Salma Ayu Safitri (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2025)
The development of digital technology has encouraged innovation in occupational safety training methods, including the use of Virtual Reality (VR) as an interactive learning medium. This community service activity aimed to improve participants’ understanding of creating and implementing three-dimensional Virtual Reality for safety induction at PT. PLN Nusantara. The program was conducted on 12–13 November 2025 and involved 15 participants. The implementation stages included preparation, material socialization, practical training on 3D VR simulation development, and evaluation. During the practical session, participants learned to create simple virtual objects, design safety simulation environments, and operate VR devices to display interactive simulations. The results showed an improvement in participants’ understanding of Virtual Reality concepts, VR device operation, and the implementation of digital-based safety induction media. The use of VR provided a more engaging and realistic learning experience compared to conventional methods. This activity is expected to become an initial step toward the development of technology-based occupational safety training media in industrial environments.